Effect of Joule-Thomson pressure drop on a cryogenic three fluid heat exchanger with two communications. (March 2020) - Chodankar, Vishnudas A.V.L.; Aswatha,; Krishna, V.; Seetharamu, K.N.
Highlights: Joule-Thomson effects are prominent in cryogenic heat exchangers. Positive Joule-Thomson effect shows an increase in effectiveness and negative Joule-Thomson effect shows a decrease in effectiveness. Joule-Thomson effects are more prominent at hot fluid. Abstract: In most cryogenic heat exchangers pressure drop effects are neglected during the design stage. However, if the heat exchanger requirements are stringent the pressure loss should be considered. The present paper investigates the thermal aspect of pressure drop, which is totally different from the previous researches which only focused on the hydraulic aspect of the pressure drop. Here the finite element method is used to study the effect of Joule-Thomson pressure drop on three stream cryogenic heat exchanger. This study is conducted considering six dimensionless parameters, of which one to account for Joule-Thomson pressure drop. The effects of these dimensionless parameters on the behavior of hot fluid is studied, presenting valuable information towards better understanding of hot fluid behavior.